A rare move: the effects of switching from a closing call auction to a continuous trading - Chang,Ya-Kai; Chou,Robin K; Yang,Jimmy (The Journal of Futures Markets, 2020)
This study investigates the effects of switching to a closing continuous trading (CCT) on market quality, while considering the trading behaviors of different types of traders. Investors become more patient in the period preceding the last trading phase, which reduces the bid–ask spread (BAS) in that period. We find an increase in the BAS and volatility during the last trading phase, due to diminishing investor patience. Market volatility and the closing pricing errors relate positively to the trading activities of foreign institutional investors. Overall, the introduction of the CCT worsens the market quality before the closing.
Keywords: Finance